1998
DOI: 10.1038/sj.bjc.6690041
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation in the promoter region of the p16 (CDKN2/MTS-1/INK4A) gene in human breast tumours

Abstract: SummaryThe p16 (CDKN2/MTS-1/INK4A) gene is one of several tumour-suppressor genes that have been shown to be inactivated by DNA methylation in various human cancers including breast tumours. We have used bisulphite genomic sequencing to examine the detailed sequence specificity of DNA methylation in the CpG island promoter/exon 1 region in the p16 gene in DNA from a series of human breast cancer specimens and normal human breast tissue (from reductive mammaplasty). The p16 region examined was unmethylated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 34 publications
(52 reference statements)
0
25
1
3
Order By: Relevance
“…The question that now remains to be answered is whether breast cancer Given that BRCA1 is recognized as an important susceptibility gene, it can be assumed that both epigenetic modifications and mutations participate in the initiation of an oncogenic phenotype 85 . Other tumor-suppressor genes, such as CDKN2A and PTEN, undergo CpG island promoter methylation, but in normal cells, the promoter region is unmethylated 86,87 . Epigenetic studies have revealed that breast cancer subtypes display different methylation profiles and are epigenetically distinct 88 .…”
Section: Tumor Microenvironment and Intra-tumor Heterogeneitymentioning
confidence: 99%
“…The question that now remains to be answered is whether breast cancer Given that BRCA1 is recognized as an important susceptibility gene, it can be assumed that both epigenetic modifications and mutations participate in the initiation of an oncogenic phenotype 85 . Other tumor-suppressor genes, such as CDKN2A and PTEN, undergo CpG island promoter methylation, but in normal cells, the promoter region is unmethylated 86,87 . Epigenetic studies have revealed that breast cancer subtypes display different methylation profiles and are epigenetically distinct 88 .…”
Section: Tumor Microenvironment and Intra-tumor Heterogeneitymentioning
confidence: 99%
“…Four independent studies analyzing breast cancer, prostate cancer, and brain lymphoma have reported methylation of non-CpG sites (mostly CpNpG sites, where N indicates A, C, T, or G) in the CDKN2A promoter. [20][21][22][23] NonCpG methylation has been reported at other important cancerrelated genes, such as GSTP1 24 and TP53 25 in endometrial and lung cancer specimens, respectively. Whether non-CpG methylation is a contributing factor or a consequence of these diseases is currently unclear.…”
Section: Evidence For Non-cpg Methylation In Mammalian Cellsmentioning
confidence: 99%
“…A high proportion (37.3%) of hypermethylated alleles were present in our breast carcinomas and all three islands were simultaneously hypermethylated in all hypermethylated tumors. To further explore whether there was variation in methylation status at dierent CpG sites in the same CpG island (as seen in hypermethylated p16, Gonzalgo et al, 1997;Woodcock et al, 1999), the methylation pattern of individual CpG sites was examined in greater detail by bisul®te-modi®ed genomic sequencing (Figure 4) in selected tumor tissues, and a uniform pattern of methylation of entire CpG sites was Figure 2 Transcriptional mechanisms suggested to be implicated in reduced/negative E-cadherin (E-cad) expression. (a) Schematic diagram of the E-cad promoter showing the 7160 polymorphic site, the E-boxes for Snail binding, and three CpG islands implicated in hypermethylation.…”
Section: Figure 1 Genetic Deletion and Mutation Of E-cadherin (E-cad)mentioning
confidence: 99%